ANALISIS LINGKUNGAN BELAJAR UNTUK MEDIA MENULIS BAGI SISWA - samosir, astuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The research data source is the results of interviews with Indonesian teachers in Jabodetabek. From the results of the research above, it can be concluded that the learning environment affects students’ writing skills. There are two learning environments, namely indoors and outdoors. The learning media used by the teacher in writing poetry are audiovisual, audio, hands-on, projects, puzzles, picture cards, and others